2023
DOI: 10.1371/journal.pntd.0010936
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica juveniles interact with the host fibrinolytic system as a potential early-stage invasion mechanism

Abstract: Background The trematode Fasciola hepatica is the most widespread causative agent of fasciolosis, a parasitic disease that mainly affects humans and ruminants worldwide. During F. hepatica infection, newly excysted juveniles (FhNEJ) emerge in the duodenum of the mammalian host and migrate towards their definitive location, the intra-hepatic biliary ducts. Understanding how F. hepatica traverses the intestinal wall and migrates towards the liver is pivotal for the development of more successful strategies again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In fact, enolase has been recently reported as the most commonly identified PLG receptor in parasitic helminths in a scoping review conducted by our group [19]. Our results also confirm those obtained twenty years ago by Bernal et al [64], who identified an enolase in the excretory/secretory products of F. hepatica as a potential 20 PLG receptor, and complement our own findings in which we characterize the potential of the tegument of F. hepatica juvenile [26] and adult worms [65] to interact with the fibrinolytic system of their host. Indeed, the utilization of this mechanism throughout the life cycle of F. hepatica could have different functions adapted to the changing environments faced by the parasite.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In fact, enolase has been recently reported as the most commonly identified PLG receptor in parasitic helminths in a scoping review conducted by our group [19]. Our results also confirm those obtained twenty years ago by Bernal et al [64], who identified an enolase in the excretory/secretory products of F. hepatica as a potential 20 PLG receptor, and complement our own findings in which we characterize the potential of the tegument of F. hepatica juvenile [26] and adult worms [65] to interact with the fibrinolytic system of their host. Indeed, the utilization of this mechanism throughout the life cycle of F. hepatica could have different functions adapted to the changing environments faced by the parasite.…”
Section: Discussionsupporting
confidence: 92%
“…rFhENO was tested in a PLG activation assay to explore the enhancement of plasmin generation by this recombinant protein following the methodology described by Serrat et al [26]. Briefly, wells containing 2 µg of human PLG (Origene) were incubated with 3 µg of D-Val-Leu-Lys 4-nitroanilide dihydrochloride chromogenic substrate (S-2251) (Sigma-Aldrich) in the presence of 1 µg of rFhENO or 1% BSA as negative control in a test volume of 100 µL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations